Congenital Sucrase–Isomaltase Deficiency: Same Mutation with Different Clinical Presentations - İssi Irlayıcı, Fatma and Güven, Burcu and Çakır, Murat (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Congenital sucrase–isomaltase deficiency is an autosomal recessive inherited disaccharidase deficiency characterized by chronic osmotic diarrhea. In this study, the genotype–phenotype relationships of close relatives of an index case with congenital sucrase–isomaltase deficiency were investigated. Materials and Methods: A 23-month-old female patient with a sucrase–isomaltase gene c.317G>A (p.C106Y) homozygous mutation was diagnosed as an index case and her pedigree analysis was performed subsequently. The family members with and without sucrase– isomaltase gene mutations were compared in terms of clinical symptoms. Results: The study included 109 cases [mean age ± SD: 22.6 ± 17.2 years (0.1-75 years), 61 males (56%)] of 130 family members of the index case. Sucrase–isomaltase gene c.317G>A (p.C106Y) heterozygous mutation was detected in 27 cases (24.7%); 14 (51.9%) were male and had a mean age of 23.2 ± 18.3 years. The most common complaints of 12 (44.4%) symptomatic patients with mutations were abdominal pain (37%), gas irritability (33.3%), bloating (22.2%), and foul-smelling stools (18.5%). Compared with the cases without mutation, a statistically significant difference was observed in the incidence of gas irritability, foul-smelling stool, ≥2 gastrointestinal symptoms, postprandial complaints, and food allergy (P = .005, P = .047, P = .049, P = .017, P = .021, respectively). Sacrosidase enzyme replacement was applied to 7 patients whose symptoms did not improve with dietary elimination. Clinical response was obtained after enzyme treatment. Conclusion: Despite its autosomal recessive inheritance, congenital sucrase–isomaltase deficiency can also be symptomatic in heterozygous individuals. Further studies are required to clarify the genotype–phenotype relationship and management of the disease. Cite this article as: İssi Irlayıcı F, Güven B, Çakır M. Congenital sucrase–isomaltase deficiency: Same mutation with different clinical presentations. Turk J Gastroenterol. 2024;35(4):343-349.